Digital resources and escape rooms: Innovative strategies that improve motivation - Murillo, Maria Valentina Toral; Torres, Melissa Fernandez; Muro, Karen Itzel Mexicano; Flores, Elvira Rodriguez (Journal of Education and e-Learning Research, 2025)
Innovations have been made to educational strategies in health sciences to increase intrinsic motivation in students which helps generate a significant and active learning in students with the help of methodologies, such as gamification, using escape rooms (ER) and the use of digital tools, such as the Sectra Table. The objective of this study is to determine the correlation of motivation in medical students using the Sectra Table digital tool versus nursing students who implemented escape rooms in anatomy sessions. This study was carried out at the Universidad Autónoma de Guadalajara. It is a cross-sectional study using a descriptive analysis technique for comparing samples. With a convenience sample of 72 students from the medicine and nursing program, subjecting medicine students to Sectra Table learning and nursing students to escape rooms determining the level of motivation using the RIMMS questionnaire with an alpha greater than .81 for all constructs having as independent variables, confidence, attention, relevance and satisfaction. We performed a statistical analysis by a two-sample comparison model. Obtaining that “escape room” presented higher levels of motivation and with a p-value of 0.0000 satisfaction presented greater motivation levels. Gamification prepares today’s society and helps them acquire professional skills that prepare them for life.